Internal Audit Function Characteristics and the Quality of Internal Control Systems: Moderating the Effect of Enterprise Resource Planning System Maturity - Shaiti, Hani; Al-Matari, Yahya (Asian Economic and Financial Review, 2020)
The aim of this study is to investigate the relationship between the internal audit function (IAF) (independence and competence) and the quality of internal control systems (ICSQ). It also aims to assess the moderating role of the maturity of enterprise resource planning (ERP) on these relationships. Using data from 98 Saudi Arabian small and medium-sized enterprises (SMEs) that have implemented an ERP system, this paper uses a Structural Equation Model to examine the hypotheses. In particular, the Partial Least Squares Structural Equation Modelling (PLS-SEM) is adopted for data analysis and hypothesis testing. The results reveal that both internal audit competence and independence are positively associated with ICSQ. Moreover, the maturity of ERP moderates the relationship between internal audit competence and ICSQ. These ﬁndings have signiﬁcant implications with regard to the ICSQ, as the identification of the internal audit function’s characteristics affects the internal control quality of SMEs. In addition, the ﬁndings have implications on those who are concerned with measuring ICSQ, such as company managers and regulatory bodies. This study uses the COSO framework to measure ICSQ.